2020
DOI: 10.1093/cid/ciaa1033
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Sexually Transmitted Infection Screening Among Men who Have Sex with Men in Pre-exposure Prophylaxis (PrEP) Care in the United States

Abstract: Background The U.S. Centers for Disease Control and Prevention (CDC) recommends comprehensive sexually transmitted infection (STI) screening every 3–6 months for men who have sex with men (MSM) using HIV preexposure prophylaxis (PrEP). The gaps between these recommendations and clinical practice by region have not been quantified. Methods We used survey data collected from the internet-based ARTnet study between 2017 and 2019… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…However, it is not clear whether these findings relating to STD and HIV testing are unique to the pandemic because studies before the pandemic have also found imperfect compliance to STD and HIV testing guidelines for PrEP users. 15,16 Moreover, the pandemic's influence on PrEP use itself is inconclusive; a fifth of participants either indicated they discontinued PrEP use or changed how often they take PrEP because of COVID-19, but there were minimal changes in the number of missed PrEP doses among those who remained on PrEP across periods.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear whether these findings relating to STD and HIV testing are unique to the pandemic because studies before the pandemic have also found imperfect compliance to STD and HIV testing guidelines for PrEP users. 15,16 Moreover, the pandemic's influence on PrEP use itself is inconclusive; a fifth of participants either indicated they discontinued PrEP use or changed how often they take PrEP because of COVID-19, but there were minimal changes in the number of missed PrEP doses among those who remained on PrEP across periods.…”
Section: Discussionmentioning
confidence: 99%
“…The difference to our results might be due to differences in data capture and healthcare systems. A US survey showed that regular STI screening was offered to 57–87% of PrEP users depending on the sampling location [ 19 ]. In a survey from the United Kingdom, self-reported HIV/STI testing frequencies were high among PrEP users in a trial or a PrEP programme but lower for users sourcing PrEP privately (HIV: 58% reported ≥ 3 tests/year; STI: 48% reported ≥ 3 tests/year) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated testing frequencies outside structured PrEP programmes. Data from surveys and insurance claims indicate considerable differences between guideline recommendations and actual testing frequencies [ 19 - 23 ]. Using PrEP from informal sources (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Higher STI case rates in San Francisco may reflect increased screening for STIs among PrEP users. 28 However, recent modeling has suggested that PrEP STI screening could decrease STI incidence through this improved case detection. 29…”
Section: Discussionmentioning
confidence: 99%